(Re)production of Inequalities in Retirement Practices and Meanings Assigned to the Term ‘Retiree’ in the Post-Communist Context - Urbaniak, Anna (Frontiers in Sociology, 2021)
In the institutionalised life course transition from work to retirement is the transition that culturally defines the beginning of later life. However, there is no universal way of experiencing retirement or understanding retirees’ social roles. Especially in the context of the post-communist, liquid modern reality in Poland. The social role of the retiree, defined as a set of rules and expectations generated for individuals occupying particular positions in the social structure, is constructed at the intersection of what is culturally defined and individually negotiated. Therefore, the way in which individuals (re)define term ‘retiree’ and ‘do retirement’ reflects not only inequalities in individual resources and attitudes, but also in social structure in a given place and at a given time. In this contribution, I draw upon data from 68 qualitative interviews with retirees from Poland to analyse retirement practices and meanings assigned to the term ‘retiree’. Applying practice theory, I explore the inequalities they (re)produce, mirror and reinforce at the same time. Results show that there are four broad types of retirement practices: caregiving, working, exploring and disengaging. During analysis of meanings assigned by participants to the term ‘retiree’, two definitions emerged: one of a ‘new wave retiree’ and the other of a ‘stagnant retiree’. Results suggest that in the post-communist context, retirement practices and meanings assigned to the term ‘retiree’ are in the ongoing process of (re)negotiation and are influenced on the one hand by the activation demands resulting from discourses of active and productive ageing, and on the other by habitus and imaginaries of retirement formed in the bygone communist era. Retirement practices and definitions of the term ‘retiree’ that emerged from the data reflect structural and individual inequalities, highlighting intersection of gender, age and socioeconomic status in the (re)production of inequalities in retirement transition in the post-communist context.